Integration and disintegration: Serbian monophony in a polyphonic context - Moody Ivan (Muzikologija, 2011)
The venerable arguments concerning the validity of harmonized music in the Orthodox Church continue. Serbia is unique in that the codifiers of the monophonic repertoire (in particular Stankoviš and Mokranjac) were also the initiators of the harmonic tradition. Comparison with Bulgaria and Romania prove that there are parallels elsewhere, but the systematic quality of the work of both Stankoviš and Mokranjac is unique. The character of Mokranjac's work in particular is determined by the working out of the harmonic and melodic implications of the monophonic tradition.